2015
DOI: 10.1097/aln.0000000000000656
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Autophagy and Ventilator-induced Diaphragmatic Dysfunction

Abstract: In this model of VIDD, autophagy is induced by MV but is not responsible for diaphragmatic weakness. The authors propose that autophagy may instead be a beneficial adaptive response that can potentially be exploited for therapy of VIDD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 39 publications
2
50
1
Order By: Relevance
“…In the present study we observed an upregulation of mRNA transcripts for LC3B and other autophagy‐associated genes in concert with reduced LC3B‐II protein levels in MV diaphragms. This constellation of changes is consistent with an accelerated rate of autophagosome formation and degradation, respectively (i.e., increased autophagic flux) . Interestingly, autophagy has been reported to be defective in mdx mouse muscles under basal conditions, whereas pharmacological activation of autophagy ameliorates dystrophic manifestations .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In the present study we observed an upregulation of mRNA transcripts for LC3B and other autophagy‐associated genes in concert with reduced LC3B‐II protein levels in MV diaphragms. This constellation of changes is consistent with an accelerated rate of autophagosome formation and degradation, respectively (i.e., increased autophagic flux) . Interestingly, autophagy has been reported to be defective in mdx mouse muscles under basal conditions, whereas pharmacological activation of autophagy ameliorates dystrophic manifestations .…”
Section: Discussionsupporting
confidence: 73%
“…Interestingly, autophagy has been reported to be defective in mdx mouse muscles under basal conditions, whereas pharmacological activation of autophagy ameliorates dystrophic manifestations . Moreover, we have previously reported that stimulation of autophagy in non‐dystrophic mice is associated with prevention of diaphragmatic weakness during the early stages of VIDD . Therefore, activation of autophagy could potentially help to mitigate MV‐induced force loss in the dystrophic diaphragm, although this hypothesis requires formal testing in future studies.…”
Section: Discussionmentioning
confidence: 93%
“…Overall, this aspect of VIDD may open new therapeutic avenues as the redox state of a cell might theoretically be influenced positively . Recent data indicate protection from diaphragmatic weakness with N‐acetylcysteine via augmented autophagosome formation in mice …”
Section: Pathophysiology Of Respiratory Muscles Dysfunction and Vidd:mentioning
confidence: 99%
“…97 Currently, no medical treatment for VIDD is available. 126 Anti-oxidants show benefits in animal models 40,71,72,127 and in a randomized trial in critically ill surgical patients. 128 However, human data remain sparse.…”
Section: Vidd Management: a Role For Ventilatory And Pharmacological mentioning
confidence: 99%
See 1 more Smart Citation